Targeting n-3 Polyunsaturated Fatty Acids in Non-Alcoholic Fatty Liver Disease - Valenzuela, Rodrigo; Ortiz, Macarena; Hernández-Rodas, María C.; Echeverría, Francisca; Videla, Luis Alberto (Current Medicinal Chemistry, 2020)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is characterized by abnormal hepatic accumulation of triacylglycerides in the absence of alcohol consumption, in association with Oxidative Stress (OS), a pro-inflammatory state and Insulin Resistance (IR), which are attenuated by n-3 long-chain polyunsaturated Fatty Acids (FAs) C20-C22 (LCPUFAs) supplementation. Main causes of NAFLD comprise high caloric intake and a sedentary lifestyle, with high intakes of saturated FAs. Methods: The review includes several searches considering the effects of n-3 LCPUFAs in NAFLD in vivo and in vitro models, using the PubMed database from the National Library of Medicine- National Institutes of Health. Result: The LCPUFAs eicosapentaenoic acid (C20:5 n-3, EPA) and docosahexaenoic acid (C22:6 n- 3, DHA) have a positive effect in diminishing liver steatosis, OS, and the levels of aspartate aminotransferase, alanine aminotransferase and pro-inflammatory cytokines, with improvement of insulin sensitivity and adiponectin levels. The molecular pathways described for n-3 LCPUFAs in cellular and animal models and humans include peroxisome proliferator–activated receptor-α activation favouring FA oxidation, diminution of lipogenesis due to sterol responsive element binding protein-1c downregulation and inflammation resolution. Besides, nuclear factor erythroid-2-related factor-2 activation is elicited by n-3 LCPUFA-derived oxidation products producing direct and indirect antioxidant responses, with concomitant anti-fibrogenic action. Conclusion: The discussed effects of n-3 LCPUFA supplementation support its use in NAFLD, although having a limited value in NASH, a contention that may involve n-3 LCPUFA oxygenated derivatives. Clinical trials establishing optimal dosages, intervention times, type of patients and possible synergies with other natural products are needed in future studies.
Keywords: anti-lipogenic mechanism